The Influence of Accessibility and Cultural Events Organized by the Lake Toba Authority Implementing Agency on the Decision to Visit Toba Caldera Resort - Wulandari, Odilia Trasrasa Indah; Siregar, Indra (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of accessibility and cultural events organized by the Lake Toba Authority (BPODT) on tourists' decision to visit Toba Caldera Resort. The research is based on the growing importance of Toba Caldera Resort as a part of Indonesia's National Tourism Strategic Areas (KSPN), developed to become a leading destination in North Sumatra, particularly in the cultural tourism sector and the MICE industry (Meeting, Incentive, Convention, and Exhibition). A quantitative approach was used with a survey method. The sampling technique employed was non-probability sampling with an accidental sampling approach involving 100 respondents who met the criteria: having visited Toba Caldera Resort and attended at least one cultural event in the area. The research instrument was a Likert-scale questionnaire, which was tested for validity and reliability. Data analysis involved classical assumption tests (normality, multicollinearity, and heteroskedasticity), multiple linear regression, t-test, F-test (ANOVA), and coefficient of adjusted determination (R²) using SPSS. The results show that accessibility (X1) has a significant effect on the decision to visit, with a significance value of 0.000, a t-value of 15.480, and a beta coefficient of 0.774. Cultural events (X2) also have a significant effect, with a significance value of 0.000, a t-value of 5.931, and a b eta of 0.296. Simultaneously, both variables significantly influence the decision to visit, with an F-value of 157.573 and significance of 0.000. The adjusted R Square value of 0.760 indicates that 76.0% of the variance in visit decisions can be explained by these two variables, while the remaining 24.0% is influenced by other factors not included in the model. This study concludes that improving accessibility and organizing attractive and consistent cultural events are effective strategies to enhance destination appeal and increase tourist visits to Toba Caldera Resort.